Clinical and Molecular Epidemiology of Human Parainfluenza Viruses 1–4 in Children from Viet Nam - Linster, Martin; Do, Lien Anh Ha; Minh, Ngo Ngoc Quang; Chen, Yihui; Zhe, Zhu; Tuan, Tran Anh; Tuan, Ha Manh; Su, Yvonne C. F.; van Doorn, H. Rogier; Moorthy, Mahesh; Smith, Gavin J. D. (Scientific reports, 2018)
HPIVs are serologically and genetically grouped into four species that account for up to 10% of all hospitalizations due to acute respiratory infection in children under the age of five. Genetic and epidemiological data for the four HPIVs derived from two pediatric cohorts in Viet Nam are presented. Respiratory samples were screened for HPIV1–4 by real-time PCR. Demographic and clinical data of patients infected with different HPIV were compared. We used a hemi-nested PCR approach to generate viral genome sequences from HPIV-positive samples and conducted a comprehensive phylogenetic analysis. In total, 170 samples tested positive for HPIV. HPIV3 was most commonly detected in our cohort and 80 co-detections of HPIV with other respiratory viruses were found. Phylogenetic analyses suggest local endemic circulation as well as punctuated introductions of new HPIV lineages. Viral gene flow analysis revealed that Viet Nam is a net importer of viral genetic diversity. Epidemiological analyses imply similar disease severity for all HPIV species. HPIV sequences from Viet Nam formed local clusters and were interspersed with sequences from diverse geographic regions. Combined, this new knowledge will help to investigate global HPIV circulation patterns in more detail and ultimately define more suitable vaccine strains.